2016
DOI: 10.1002/ajp.22574
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization and performance asymmetries in the termite fishing of wild chimpanzees in the goualougo triangle, republic of Congo

Abstract: The nearly universal right hand preference manifested by human populations is one of the most pronounced manifestations of population-level lateralization. Morphological and archeological evidence indicate that this behavioral specialization may have emerged among our hominin ancestors. Whether population-level behavioral asymmetries are evident in non-human animals remains a topic of considerable scientific debate, with the most consistent evidence of population-level trends emerging from studies of chimpanze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 90 publications
2
27
3
Order By: Relevance
“…First, we found no evidence of population-level handedness for this behavior, which differs from findings on hand use for termite-fishing in wild chimpanzees, which is the task our measure was designed to simulate [72,83–86]. The results also differ from findings of population-level handedness for other types of tasks in captive chimpanzees [87].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…First, we found no evidence of population-level handedness for this behavior, which differs from findings on hand use for termite-fishing in wild chimpanzees, which is the task our measure was designed to simulate [72,83–86]. The results also differ from findings of population-level handedness for other types of tasks in captive chimpanzees [87].…”
Section: Discussioncontrasting
confidence: 90%
“…One way to address this issue would be for researchers to focus on assessing, not just hand preferences, but performance asymmetries for any given task as a means of validating their sensitivity to potential underlying functional asymmetries. Measures of performance asymmetries in hand use is fairly uncommon in research on laterality involving nonhuman primates [6772] and this could 0be a fruitful area for further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lonsdorf and Hopkins [2005] suggested that left hand preference was more prevalent than right hand preference (task specialization) among the Kasekela community. Central chimpanzees (P. troglodytes troglodytes) in the Goualougo Triangle exhibited strong individual hand preference when termite fishing; however, there was no significant overall population-level bias [Sanz et al, 2016]. Collectively, these data suggest that termite fishing elicits strong hand preference.…”
Section: Introductionmentioning
confidence: 58%
“…Among captive bonobos, we predicted that bimanual asymmetrical grooming would elicit hand preference given its increased complexity, whereas unimanual grooming would not [Fagot and Vauclair, 1991;Hopkins, 1995;Leca et al, 2011]. Based on tool use data from captive bonobos [Chapelain et al, 2011;Hopkins et al, 2011;Bardo et al, 2015;Hopkins et al, 2015] and wild chimpanzees Marchant 1992, 1996;Lonsdorf and Hopkins, 2005;Bogart et al, 2012;Sanz et al, 2016], we anticipated significant individual hand preference for tool use. While Bardo et al [2015] found task specialization in a food extraction task among captive bonobos, this group bias has only been demonstrated in some studies of wild chimpanzees.…”
Section: Introductionmentioning
confidence: 99%